2022
DOI: 10.3389/fpubh.2022.862407
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Artificial Intelligence on the Mental Health of Manufacturing Workers: The Mediating Role of Overtime Work and the Work Environment

Abstract: BackgroundWork-related mental health and psychological injuries are important issues related to people's livelihood and wellbeing. Currently, digitalization and intelligent technology have an extremely large impact on the workforce. China is actively promoting the deep integration of artificial intelligence (AI) and manufacturing, which may have important implications for the mental health of manufacturing workers. However, existing researches have paid little attention to the influence of AI on the mental wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…Their research found that AI could reduce psychological depression levels by scores of 1.643 points which shows the technology supports the workers' mental wellbeing (Wei & Li, 2022). This effect would, however, vary by proficiency level and generation.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Their research found that AI could reduce psychological depression levels by scores of 1.643 points which shows the technology supports the workers' mental wellbeing (Wei & Li, 2022). This effect would, however, vary by proficiency level and generation.…”
Section: Related Workmentioning
confidence: 97%
“…Other researchers would explain the effect of integrating AI in the working environment to deal with employees' mental health, specifically from the standpoint of labor-capital relationships. Wei & Li (2022) conducted a survey using statistics from the 2018 China Labor Force Dynamics Survey to assess the effect of AI on the depressing indicators of workers within the manufacturing sector.…”
Section: Related Workmentioning
confidence: 99%
“…4 These changes have the potential to shape work environments to which workers are exposed and thereby impact worker health outcomes. 28 AI within the workplace can be used to automate physically and psychologically demanding job tasks. 29 However, AI can also contribute to workplace hazards for human workers such as the intensification of work and performance pressures (e.g., increasing pace of work to keep up with productive AI), loss of job autonomy (e.g., AI takes control over the performance of job tasks) and the psychosocial stressors arising from the fear of being made obsolete as AI fully automates a job.…”
Section: Health Safety Well-being and Equity Implications Of Ai In Th...mentioning
confidence: 99%
“…AI will change the nature of work including the design of workplaces, performance of job tasks, and the demand for workers in certain occupations 4 . These changes have the potential to shape work environments to which workers are exposed and thereby impact worker health outcomes 28 . AI within the workplace can be used to automate physically and psychologically demanding job tasks 29 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rathnayaka et al [7] proposed a chatbot with cognitive skills to provide recurrent emotional support, personalised assistance, and remote mental health monitoring. Wei and Li [8] demonstrated that AI can reduce the depression of manufacturing workers in China. Deshpande and Rao [9] also utilize emotion AI to detect depression from Twitter feeds using a natural language processing technique.…”
Section: State-of-the-art Of Ai and Emotions Recognitionmentioning
confidence: 99%